Enhancing Training Effectiveness: Evaluating the Blended Learning Method in Basic Training for Probationary Civil Servants at the Ministry of Transportation - Febrina, Rima; Ekowati, Adhani; Bandiah, Bandiah (Majalah Ilmiah Bijak, 2025)
In accordance with PerKALAN 14/2022 Latsar CPNS Training Curriculum, the implementation of Latsar CPNS can be carried out with a full online, hybrid, or face-to-face learning model. The Ministry of Transportation organizes Latsar CPNS with a hybrid method which is divided into 3 phases: MOOC-Online Learning-Classical. This change in the learning model is said to have pros and cons because on the one hand it provides cost efficiency and the number of graduates but is felt to reduce the achievement of learning objectives. In this study, an analysis was conducted on the perceptions from the perspective of Latsar CPNS alumni regarding the 3 learning phases. The results were that the MOOC and Online phases with facilitators were quite effective with the lowest average value in the efficiency dimension.   Learning ineffectiveness occurs, especially due to network constraints for employees in 3T areas or conflict areas and provisions for being free from duties during Latsar which cannot be carried out because assignments, leader’s direction, and services at the workplace must continue. Meanwhile, strengthening the effectiveness of learning occurred more during the classical stage because teachers and participants could explore more material, issues/cases, and best practices.